Les émissions d'obligations dans le droit de la province de Québec de 1890 à nos jours - Le Bel, Suzanne (Les Cahiers de droit, 1980)
In the last decade of the 19th century, the English law of securities had already reached an advanced stage of development. Reception of that law seemed desirable throughout the British Empire. In Quebec, however, wholesale introduction of English concepts and rules could not easily be reconciled with the civil law system. This paper shows how the English law of securities, as it was perceived by writers and judges in Canada, gradually gained currency in many provincial incorporating statutes. This process culminated in the enactment by the Quebec Legislature of the Special Corporate Powers Act of 1914. The paper concludes with a description of the contents of this Act and its evolution up to the present day.